The Role of Ergonomic Interventions in Enhancing Employee Well-being: A Case Study from the Hospitality Industry - Irwanti, Ni Ketut Dewi; Adiatmika, I Putu Gede; Muliarta, I Made; Abdullah, Dahlan (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
The impact of ergonomic interventions and multitasking on employee well-being, particularly in high-demand hospitality settings, explores how these factors interact with perceived organizational support, an essential mediator that could influence employee satisfaction, health, and productivity. This study aims to discover the relationships among ergonomic interventions, multitasking, perceived organizational support, and employee well-being, focusing on employees of the Puri Saron Hotel Group in Bali. The study employs a quantitative methodology, utilizing SEM SmartPLS 3 software. Data was collected over questionnaires spread to a sample of 100 employees, following Slovin’s formula. The findings contribute to the growing field of workplace ergonomics by demonstrating that both physical ergonomic interventions positively, with the with the highest significant impact, and followed by multitasking for employee well-being, as the study is focused on a single hospitality group, the generalizability of the results may be limited. The enhancing ergonomic conditions and multitasking abilities, coupled with strong organizational support, can significantly improve employee well-being, particularly in industries with high physical and cognitive demands. this offering valuable insights into the role of perceived organizational support in mediating these relationships.